Plant-Derived Compounds as Promising Therapeutics for Vitiligo - Pang, Yaobin; Wu, Shi; He, Yingjie; Nian, Qing; Lei, Jing; Yao, Yejing; Guo, Jing; Zeng, Jinhao (Frontiers in Pharmacology, 2021)
Vitiligo is the most common depigmenting disorder characterized by white patches in the skin. The pathogenetic origin of vitiligo revolves around autoimmune destruction of melanocytes in which, for instance, oxidative stress is responsible for melanocyte molecular, organelle dysfunction and melanocyte specific antigen exposure as well as melanocyte cell death and thus serves as an important contributor for vitiligo progression. In recent years, natural products have shown a wide range of pharmacological bioactivities against many skin diseases, and this review focuses on the effects and mechanisms of natural compounds against vitiligo models. It is showed that some natural compounds such as flavonoids, phenols, glycosides and coumarins have a protective role in melanocytes and thereby arrest the depigmentation, and, additionally, Nrf2/HO-1, MAPK, JAK/STAT, cAMP/PKA, and Wnt/β-catenin signaling pathways were reported to be implicated in these protective effects. This review discusses the great potential of plant derived natural products as anti-vitiligo agents, as well as the future directions to explore.